Governance on provision of ecosystem and its services in Nepal: Lessons from appraisal of policy, legislation, and institution - Pashupati Nepal; Basanta Paudel; Yili Zhang; Narendra Raj Khanal; Linshan Liu; Mohan Kumar Rai; Nirdesh Nepal (Geography and Sustainability)
Ecosystem degradation and the loss of ecosystem services stem from multiple causes, requiring coordinated and diverse policies, legislation, and institutional responses to effectively address them. An understanding of the policies, legislation, and institutions governing ecosystem services can enhance the sustained management and provision of ecosystem services. Therefore, this work appraises the policies, legislation and institutional provisions made by the government of Nepal. In addition, this study analyzes policy implications and identifies gaps and barriers that hinder future improvements in the management of ecosystem services. Altogether, 63 documents comprising 45 policies and 18 legislations promulgated by the government of Nepal have been assessed for content analysis. Twenty Key Informant Interviews (KIIs) have also been conducted to obtain expert insights about the gaps in policy formulation and implementation. The results indicate that though several sectoral policies and legislations have made provision on management of ecosystem and its services implicitly or explicitly, still there is lacking of overarching framework to deal with ecosystem services. Overlapping roles and responsibilities outlined in the constitution, policies, and legislation, coupled with weak enforcement and lack of multisectoral coordination mechanism, are significant obstacles to effective policy implementation. Therefore, there is a need to develop an overarching national framework backed up by legislation with a strong multisectoral coordination mechanism that will adopt a holistic and multidisciplinary approach to the sustained management and provision of the ecosystem and its services.